Shared Decision Making in Clinical Practice - Janneke Noordman; Mariska Oosterveld-Vlug; Jany Rademakers (University of Zurich, IKMZ - Department of Communication and Media Research, 2022)
Shared Decision Making (SDM), currently considered a preferred model for making decisions in healthcare, requires that patients have the knowledge and skills to actively participate in the consultation and decision-making process. Patients with limited health literacy (LHL) often fail to do so. To gain insight into the experiences, needs and support for LHL-patients concerning SDM in clinical practice, five focus groups were held with 26 patients with LHL. A focus group discussion guide was developed based on 4-steps SDM models. Data was coded using thematic content analyses. LHL patients participating in this study had little experience with SDM in practice, but do prefer it. Important barriers for this are healthcare provider-related (involving patients too little in decision-making, using medical jargon), patient-related (feeling insecure to play a role in decision-making, inability to understand their diagnosis or information about treatment options), patient-provider interaction-related (relationship of trust) or system-related (too little consultation time). For SDM to take place more often, a shared responsibility between patients and healthcare providers is required. We recommend expanding the SDM models, by adding a step zero (patients understand their diagnosis) and a fifth step (reviewing the decision), to improve the process for LHL patients.